Pharmacokinetic-Pharmacodynamic interaction associated with venlafaxine-XR remission in patients with major depressive disorder with history of citalopram / escitalopram treatment failure - Ahmed, Ahmed T; Biernacka, Joanna M; Jenkins, Gregory; Rush, A John; Shinozaki, Gen; Veldic, Marin; Kung, Simon; Bobo, William V; Hall-Flavin, Daniel K; Weinshilboum, Richard M; Wang, Liewei; Frye, Mark A (Journal of affective disorders, 2019)
Highlights•This study highlights the association between prospectively confirmed SNRI treatment remission and genetic polymorphisms in CYP2D6, CYP2C19, SLC6A4, and SLC6A2 in MDD patients with prospectively confirmed prior SSRI treatment failure. •Pharmacokinetic and Pharmacodynamic interaction is associated with venlafaxine-XR treatment remission. •These results underscore the multidimensional aspects of precision medicine as an approach to optimize drug treatment of MDD.